Characterizations of cupric oxide thin films on glass and silicon substrates by radio frequency magnetron sputtering - P.K., Ooi; C.G., Ching; M.A., Ahmad; S.S., Ng; M.J., Abdullah; H., Abu Hassan; Z., Hassan (Universiti Kebangsaan Malaysia, 2014)
Cupric oxide (CuO) thin films were prepared on a glass and silicon (Si) substrates by radio frequency magnetron sputtering system. The structural, optical and electrical properties of CuO films were characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), Fourier transform infrared spectrometer, ultra-violet visible spectrophotometer, respectively, four point probe techniques and Keithley 4200 semiconductor characterization system. The XRD result showed that single phase CuO thin films with monoclinic structure were obtained. AFM showed well organized nano-pillar morphology with root mean square surface roughness for CuO thin films on glass and Si substrates were 3.64 and 1.91 nm, respectively. Infrared reflectance spectra shown a single reflection peak which is corresponding to CuO optical phonon mode and it confirmed that only existence of CuO composition on both substrates. The optical direct band gap energy of the CuO film grown on glass substrate, which is calculated from the optical transmission measurement was 1.37 eV. Finally, it was found that the deposited CuO films are resistive and the palladium formed ohmic contact for CuO on glass and schottky contact for CuO on Si.